A simulator for the course of Elecromechanical Control Techniques - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2008)
This study describes a simulator as an educational tool for the course of Electromechanical Control Techniques (ECT). The course, ECT, and its counterparts with some other different names are available within the curricula of faculties and high schools, such as Technical Education Faculties in Turkey, Faculties of Engineering Technology in the USA and European Countries. Since single/three phase power system is generally used in the applications of this course, students are always faced with a high voltage and current. A simulator is developed to establish a safety study environment. In this environment, students easily implement their designs or assignments to get familiar with the real applications in the laboratory.
Keywords: electrical control techniques simulator; educational tool; educational simulators; electromechanical systems; electrical motor control; FUZZY-LOGIC CONTROLLER; EDUCATIONAL-TOOL